Pengaruh ROA Dan Ukuran Perusahaan Terhadap Audit Delay Pada Perusahaan Manufaktur Subsektor Industri Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Fika Hidayah Najah; Suhono Suhono (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to analyze the effect of Return On Asset (ROA) and Company Size on Audit Delay partially and simultaneously in the Food and Beverage Industry Sub-Sector listed on the Indonesia Stock Exchange (BEI) 2014-2018. The independent variables used in this study are Return On Assets (ROA) and Company Size. Editing the dependent variable used in this study is Audit Delay. Sampling was done by purposive sampling and get 14 companies that become samples with 70 observational data. The research method used is a quantitative method with a descriptive approach. The data analysis method used is statistical analysis using SPSS software. The results showed partially Return On Asset (ROA) has an effect on Audit Delay. And company size has no effect on audit delay partially. While the results of the study show that sig F is 0.000 <0.05, which means that Return On Assets (ROA) and Company Size have a significant effect on Audit Delay simultaneously. Keywords: Return On Assets, Company Size, Audit Delay